MNGI-02. SUBCENTIMETER MENINGIOMAS – IS IT OKAY TO IGNORE?. (5th November 2018) - Yuen, Carlen; Castillo-Saavedra, Laura; Wilmington, Andrew; Walker, Matthew; Kamson, David
Abstract: BACKGROUND: Meningiomas are among the most common incidental neuroimaging findings. Although most are indolent, a subgroup of meningiomas will eventually warrant clinical intervention. While larger diameters (e.g. ≥2.5cm) predict more aggressive behavior, there is a paucity of data regarding how much surveillance smaller meningiomas require if any. PURPOSE: To assess radiographic features of subcentimeter meningiomas that may predict future progression. METHODS: We included asymptomatic treatment naïve patients with subcentimeter probable meningiomas who had ≥6 months of MRI follow-up. Progression was defined as reaching the 1cm threshold or becoming symptomatic. Imaging characteristics such as presence of calcification, perilesional edema, T2-weighted intensity were assessed in relationship to tendency to progress via log-rank. RESULTS: Thirty-nine patients (mean age 62y, 34F) were identified, who had a total follow-up of 251 years. Twenty-four patients (60%) remained subcentimeter by the end of follow-up. Median time to reach 1cm was 3.0 years for the remaining 15 patients. Only 2 enlarged to 1.5cm, a 69-year-old female who reached this size after 4.5 years and a plateaud on subsequent scans. The other was a 71-year-old male whose tumor doubled about every 3 years, leading to resection after 7 years at 33mm. He harbored a grade 2 meningioma. None of the patients became symptomatic during the follow-up period. None of the patient's lesions had peritumoral edema. T2W intensity did not predict progression. In contrast, only 1 patient with a calcified meningioma reached 1cm. Calcification predicted slower progression (12.1 vs 6.8 years, log-rank p=0.03). CONCLUSION: Our data corroborates that most subcentimeter meningiomas grow extremely slowly. A single scan confirming calcification in the tumor may further support this growth pattern. However, repeated imaging seems necessary to identify exponential growth pattern, which is associated with higher grade meningiomas that can still present in this population.